The Role of Agriculture in Economic Development: proceedings of the eleventh international conference of Agricultural Economists (London Oxford University Press, 1963)
This book is the proceedings of the eleventh international conference of Agricultural Economists on the role of Agriculture in economic development.
uaa 22/01/19
Loans
Keywords: Agricultural Economics; London